E-Services: Implementation of Digital-Based Public Services in The 4.0 Era - Danu Eko Agustinova Danu; Supardi Supardi; Sutanto Tri Juni Putro Sutanto; Riko Septiantoko Riko (CV. Media Digital Publikasi Indonesia, 2023)
Globalization has numerous significant impacts that have an effect on people's lives. One of these impacts is the advancement of information and communication technology, which has many promising benefits, such as time efficiency, speedy delivery of information, transparency, and affordability. Technological advancements have infiltrated various sectors, including the government. In today's era of regional autonomy, it is essential to achieve good governance, which is balanced with the use of information and communication technology, commonly referred to as e-government. The use of technology and information indirectly encourages the adoption of electronic-based service systems (e-Services) in government institutions. The development of e-services is a media innovation that supports the provision of excellent services for the community, particularly in rural areas. Furthermore, the development of more varied service features such as letter submissions, complaint services, village information, and administrative procedures is expected to accelerate and facilitate access for service users more efficiently and transparently. This study aims to 1) create a public service e-service design; 2) fulfill the wishes of the community in efficient and effective village government public services; 3) understand the transparency of the village government, which can be accessed digitally. The development of letter disposition e-services in Sriharjo Village has improved the quality of public services and increased